Acute Toxicity Studies of Mirabilis jalapa L. Flower Extract in Mice - Mulyani, Isna; Desy Purnama Sari; Muhammad F. Agustiawan; Syaikhul Aziz (Gayaku Publisher, 2025)
Traditional medicine, derived from medicinal plants, has been used for generations as a form of treatment. The safety, quality, and efficacy of plants used for medicinal purposes are important considerations. Mirabilis jalapa L., also known as the four o'clock flower, is a traditional medicine with known benefits such as diuretic, anti-inflammatory, and antibacterial properties. However, its safety level remains uncertain. To address this, an acute toxicity test was conducted on the ethanol extract of Mirabilis jalapa L. flowers to determine its safety. The extraction process utilized a reflux method with 96% alcohol as a solvent, resulting in a standardized extract. Subsequent toxicity tests were performed on 12 female white mice, using doses of 300 and 2,000 mg/kg body weight. The results revealed an LD50 value exceeding 2,000 mg/kg body weight for the ethanol extract of Mirabilis jalapa L. flowers, indicating its classification as